Kampanye No Drugs Untuk Mencegah Resiko Penularan HIV/AIDS - Adi Nurapandi; Intan Nur Faridah; Dandi Zaenal Mutaqin; Irma Nurinayyah; Deti Martia Ningsih; Picki Hanief Assifa; Rana; Moh. Akmal Dzulfikar; Iif Taufiq El Haque (Yayasan Inspirasi El Burhani, 2022)
Introduction: Drug abuse is closely related to crime, traffic accidents and is currently at the stage of transmission of the HIV/AIDS virus. The sharp increase in HIV prevalence among injecting drug users is caused by the use of unsterile needles and syringes coupled with the practice of group injection. Various efforts to control and prevent drugs and HIV/AIDS have been carried out, one of which is to empower the potential and knowledge of youth through youth organizations. Objective: to implement and increase knowledge to be directly and actively involved in the prevention of drug abuse and eradication in order to avoid and prevent the risk of HIV-AIDS transmission. Method: The methodology used is that this consultation is based on strategy, implementation and action, and ends with an assessment conducted at the end of the update, using the number of surveys available to the community according to the required survey needs. Result: The implementation of socialization of the dangers of drugs and the risk of HIV-AIDS to Wibawa Mukti youth organizations in Ciharalang village gave significant results because increasing youth knowledge about the dangers of injecting drugs has a role in encouraging the participation of all elements of the local community to avoid drug use. Conclussion: The implementation of socialization of the dangers of drugs and the risk of hiv-aids to youth youth organizations in the village of ciharalang gave significant results because increasing youth knowledge about the dangers of injecting drug abuse has a role in encouraging the participation of all elements of the local community to avoid drug use.